Mosby's USMLE step 1 review - Physiology - Uwe Ackermann (Mosby, 1996)
The book includes hundreds of categorized questions on a free diskette and answers with rationales on physiology and pathophysiology of acid-base regulation. There are numerous two-color illustrations to enhance understanding. Summary tables, lists, and charts are included to synthesize material. Icon are provided to provide quick access to information